SCIENCE LITERACY IN PHYSICS LESSONS - Gulnoza Djumayeva; Asila Abduhalilova (Web of Journals Publishing, 2024)
The article is devoted to the problem of developing students' scientific literacy in teaching physics at school. A set of competencies is proposed, where special attention is paid to developing students' functional literacy and interest in the natural sciences, and through it - physics.
Keywords: Functional literacy, PISA research, set of competencies, scientific literacy, solving problems on scientific literacy, independent practical activity.